A Clinical Isolate of Candida albicans with Mutations in ERG11 (Encoding Sterol 14α-Demethylase) and ERG5 (Encoding C22 Desaturase) Is Cross Resistant to Azoles and Amphotericin B - Martel, Claire M. (American Society for Microbiology (ASM), 2010)
A clinical isolate of Candida albicans was identified as an erg5 (encoding sterol C22 desaturase) mutant in which ergosterol was not detectable and ergosta 5,7-dienol comprised >80% of the total sterol fraction. The mutant isolate (CA108) was resistant to fluconazole, voriconazole, itraconazole, ketoconazole, and clotrimazole (MIC values, 64, 8, 2, 1, and 2 μg ml(−1), respectively); azole resistance could not be fully explained by the activity of multidrug resistance pumps. When susceptibility tests were performed in the presence of a multidrug efflux inhibitor (tacrolimus; FK506), CA108 remained resistant to azole concentrations higher than suggested clinical breakpoints for C. albicans (efflux-inhibited MIC values, 16 and 4 μg ml(−1) for fluconazole and voriconazole, respectively). Gene sequencing revealed that CA108 was an erg11 erg5 double mutant harboring a single amino acid substitution (A114S) in sterol 14α-demethylase (Erg11p) and sequence repetition (10 duplicated amino acids), which nullified C22 desaturase (Erg5p) function. Owing to a lack of ergosterol, CA108 was also resistant to amphotericin B (MIC, 2 μg ml(−1)). This constitutes the first report of a C. albicans erg5 mutant isolated from the clinic.